More Than Altruism : the Politics of Private Foreign Aid. - Smith, Brian H. (Princeton legacy library., 2014)
As government officials and political activists are becoming increasingly aware, international nonprofit agencies have an important political dimension: although not self-serving, these private voluntary organizations (PVOs) and nongovernmental organizations (NGOs) seek social changes of which many of their financial contributors are unaware. As PVOs and NGOs receive increasing subsidies from their home governments in the United States, Canada, and Europe, they are moving away from short-term relief commitments in developing countries and toward longer-term goals in health, education, train.